Genotype and attachment technique influence the growth and survival of line nursery corals - Goergen, Elizabeth A.; Ostroff, Zachary; Gilliam, David S. (Restoration ecology, 2018)
The Caribbean staghorn coral, Acropora cervicornis, was once a dominant habitat creating coral, but its populations have declined dramatically in recent decades. Numerous restoration efforts now utilize coral gardening techniques to cultivate this species, growing colonies on fixed structures or from line/suspended nurseries. Line nurseries have become increasingly popular because of their small footprint and ease of use, replacing fixed structures in many nurseries. To evaluate the efficacy of the line technique, this study evaluated growth, condition, and survivorship of A. cervicornis nursery colonies of three distinct genotypes grown via two line nursery techniques (suspended and direct line attachment [vertical]). Direct line attachment of nursery colonies resulted in poor survival (43%) and growth (9.5 ± 1.33 cm/year), whereas suspended culture had 100% survival and increased growth (61.1 ± 4.19 cm/year). Suspended culture had significantly reduced disease prevalence and prevented colony predation. Suspended coral growth was also comparable to a neighboring fixed structure nursery (55.2 ± 7.86 cm/year), and found to be as effective in propagating corals as fixed structures.